The Anonymous Collective: Operations and Gender Differences. Issue 2 (3rd March 2020) - McGovern, Virginia; Fortin, Francis
Abstract : Although anyone, male, female, or nonbinary, can join the Anonymous movement or contribute to its causes, which frequently involve war, efforts to free political prisoners, and terrorism, there is clearly a central group of males who control the means of communication, such as chat rooms or Twitter accounts. Although these cyberactivists have become well known for addressing pressing social justice issues, what is not known is how the female participants in the movement function in a male-dominated cyber world. In this exploratory study, we look at the differences between the activities of male and female Anonymous members on Twitter as a way to discover similarities and differences in gendered activism. Our general objective is to identify the themes and values shared by female participants in the Anonymous movement. Our findings indicate that women focus primarily on animal rights, whereas men's tweets reflect a broader range of interests. Some possible reasons for women's attraction to animal activism are examined.